Resistensi Beberapa Isolat Bakteri terhadap Logam Berat (Hg, As, Cd, Ni, Pt dan Se) - Imamuddin, Hartati (JURNAL BIOLOGI INDONESIA, 2001)
ABSTRACTStudy of Some Bacteria to Heavy Metal Resistent (Hg, As, Cd, Ni, Pt and Se). The study was conducted to evaluate the resistance of some bacteria toward heavy metal (Hg, As, Cd, Ni, Pt and Se) by monitoring growth inhibition in Minimal Basal Medium (MBM) and Nutrient Broth (NB). Prior to growth inhibition study, pre selection of heavy metal resistance was determined by disk blanks methods. The results showed that AT 01, AT 03 and AT 11 were found to be heavy metal-resistent, however Pseudomonas sp. was a heavy metal-sensitive. The study also showed that AT 01 grew better in NB than MBM.Key words: Resistance, heavy metal, Pseudomonas sp.